Miskonsepsi Peserta Didik SMPpada Materi Operasi Hitung Bentuk Aljabar - Ianatun Nafilah Anwar; Evangelista Lus Windyana Palupi (MATHEdunesa, 2026)
The low understanding of mathematical concepts is one of the obstacles in the process of learning mathematics. The cause of this low understanding is due to misconceptions. Misconceptions in algebra arise from two factors: internal factors and external factors. Misconceptions are defined as repeated errors made by students in understanding and interpreting a concept. In line with the research objective, which is to describe junior high school students’ misconceptions in algebraic operations, this study employed a qualitative approach. The subjects consisted of 20 students out of a total of 25 who participated in the four-tier diagnostic test. Through qualitative analysis, this research can capture the context underlying students' misconceptions in algebraic operations, which may be difficult to measure with numbers or statistics. Based on qualitative analysis, several results were obtained, including: (1) The most common misconceptions experienced by students on commutative operation questions were notation misconceptions and rule application misconceptions. (2) The misconceptions experienced by students on associative operation questions included misconceptions in interpreting letters, notation, and rule application. (3) The misconceptions experienced by students on these questions involved notation and rule application misconceptions.